Penguatan Struktur Data dan Algoritma bagi Mahasiswa: Fondasi Karir Profesional di Bidang Teknologi Informasi - Huda, Nurul; Istiawan, Deden; Khikmah, Laelatul; Nur Cahyani, Annisa (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The rapid advancement of information technology demands higher education graduates to possess strong digital competencies, particularly algorithmic literacy. This form of literacy involves understanding data structures, programming logic, and computational thinking in problem-solving. This community service program aimed to strengthen algorithmic literacy among students as a foundational skill for building a professional career in the field of information technology. Conducted at the Information Technology Study Program of Universitas ‘Aisyiyah Yogyakarta, the program included need assessment, instructional material development, interactive training sessions, case-based group work, and evaluation through student presentations. The results showed significant improvement in students’ understanding of algorithms and their ability to design efficient and systematic solutions. By applying a problem-based and collaborative learning approach, students also developed essential 21st-century skills such as communication and teamwork. The case presentation-based evaluation provided comprehensive insights into their critical and logical thinking abilities. This program successfully contributed to preparing students not only as technology users but also as future innovators in the digital era.